Voltammetric determination of nitrite with gold nanoparticles/poly(methylene blue)-modified pencil graphite electrode: application in food and water samples - Koyun, Ozge; Sahin, Yucel (SPRINGER HEIDELBERG, 2018)
This work presents the preparation and characterization studies of gold nanoparticle/poly(methylene blue) (GNP/PMB)-modified pencil graphite electrode (PGE) and its use for electrochemical determination of nitrite. The working electrode (PGE) was functionalized by electropolymerization of methylene blue (MB) and modified with gold nanoparticles (GNPs) to produce the final (GNP/PMB/PGE) electrode in a two-step procedure. Characterization and morphology studies of GNP/PMB/PGE were performed by electrochemical impedance spectroscopy, cyclic voltammetry, X-ray photoelectron spectroscopy, Fourier transform Infrared spectroscopy, and scanning electron microscopy techniques. The highest peak current response was obtained for nitrite at pH 5.0. A wide linear relationship between the concentration and the oxidation peak currents of nitrite was observed in the concentration range of 5-5000 mu M. The limit of detection (0.314 mu M, S/N = 3) and reproducibility (RSD = 2.38% for N = 10) have been identified. Finally, the electrode platform was successfully applied to commercial sausage and mineral water samples.
Keywords: Nitrite; Gold nanoparticle; Poly(methylene blue); Pencil graphite electrode; Differential pulse voltammetry; GLASSY-CARBON ELECTRODE; METHYLENE-BLUE; HYDROGEN-PEROXIDE; ELECTROCHEMICAL DETERMINATION; ELECTROCATALYTIC OXIDATION; ION CHROMATOGRAPHY; PASTE ELECTRODE; LIVE CELLS; NANOPARTICLES; GRAPHENE; Chemistry; Electrochemistry; Physics